واقع رأس المال الفكري بمصنع إسمنت الفتائح في مدينة درنة من وجهة نظر العاملين به - فرج, بن خيال عبدالكريم; محمد, جبريل وائل (جامعة الوادي - University of Eloued, 2021)
الملخص : هدفت الدراسة إلى تشخيص رأس المال الفكري بمصنع الاسمنت الفتائح درنة من خلال المجالات الآتية: (رأس المال البشري، رأس المال الهيكلي، رأس مال العلاقات)، بالإضافة إلى التعرف على مدى وجود فروق معنوية لاستجابات المبحوثين حول رأس المال الفكري تعزى إلى بعض المتغيرات الديموغرافية الآتية: النوع، العمر، المستوى التعليمي، مدة الخدمة، المسمى الوظيفي، ولتحقيق أهداف الدراسة، اتبعت الدراسة منهج دراسة الحالة، فقد قام الباحثان بتطوير استبانة معتمداً على بعض الدراسات السابقة، حيث تم التأكد من مصداقيتها ومعامل الثبات لها، وقد تمثل مجتمع الدراسة في جميع العاملين بمصنع الاسمنت الفتائح بمدينة درنة، والذي بلغ قوامه (697) عاملاً، ولتحديد حجم العينة تم الاعتماد علـى جـدول krejcie and Morgan (1970)، حيث تحدد حجمها بعدد (248) عاملاً، وتم اختيارهم بطريقة العينة العشوائية البسيطة، وبعد توزيع الاستبانة تم استرجاع (174) استمارة صالحة للتحليل الإحصائي، ولتحليل بيانات الدراسة تم الاستعانة بالحاسب الآلي واستخدام برنامج إحصائي من خدمة البرمجيات الواردة في (SPSS)، حيث تم التوصل إلى العديد من النتائج يمكن إيجازها فيما يلي: كشفت الدراسة أن المستوى العام لرأس المال الفكري جاء مرتفعاً ؛ وأخيراً قدمت الدراسة مجموعة من التوصيات التي يؤمل اتباعها لتعزيز مستوى رأس المال الفكري بالمصنع محل الدراسة. Abstract: This study aims to diagnose the intellectual capital at the Cement Factory at the city of Derna, through the following themes: (Human capital, Structural capital, Relationships capital). It also aims to recognize whether there are significant morale differences between the responses of the group examined about the intellectual capital due to the following demographic variables: (gender, age, educational qualification, length of service and the job title). To achieve its objectives, the study applied the case study method; the researcher developed a questionnaire based on some previous studies, which he was sure of their validity and reliability. The study population included all employees at Al Fattaih Cement Factory, total (697) Employees, and to determine the sample size, the researcher has relied on krejcie and Morgan table (1970), the number determined as (248) Employees. They were selected by random sampling method, and after the distribution of the questionnaire, (174) valid forms were retrieval for statistical analysis. The analysis of the study data was done by computerized method using a statistical software program provided in the (SPSS). The following results were reached: the study revealed that the overall level of IC at the cement factory under study came high. Finally, the study provided a set of recommendations that will hopefully be followed in order to strengthen the level of IC at Al Fattaih Cement Factory under study.
مقال
Keywords: رأس المال الفكري، مصنع الاسمنت الفتائح، مدينة درنة (ليبيا).